IDENTIFIKASI BAKTERI ESCHERICHIA COLI PADA JAJANAN PEDAGANG KAKI LIMA DI SEKOLAH DASAR KELURAHAN BAQA, KOTA SAMARINDA - Deddy Alif Utama; Andi Sarifah Budon (CV. ADIBA AISHA AMIRA, 2024)
Street food is currently the prima donna among consumers due to its low price, accessibility, and wide variety of choices. Its distribution covers various places but is most often found in educational facilities, especially elementary schools. Various problems arise from this type of culinary contamination related to hygiene problems, especially Escherichia coli bacteria contamination. The purpose of this study was to identify E. coli contamination in snacks from street vendors (PKL) at the Baqa Village Elementary School, Samarinda City. This research uses a descriptive study design. The sample in this study consisted of 10 food and beverage samples taken from seven street vendors who were selected using a purposive sampling method and spread across all elementary schools in Baqa Village, Samarinda City. From the results of examining E. coli using the most probable number (MPN) method, it was found that the fried pentola sample from SDN 002 Samarinda Seberang exceeded the threshold value of 3.6 APM/gr, while the durian ice sample from SDN 007 Samarinda Seberang also exceeded the threshold value of 3.6 APM/ml. So it is necessary to increase comprehensive sanitation and hygiene practices for these street vendors.